Learner Agency for Autonomous Learning in Higher Education of Nepal: Beliefs and Practices of English Language Learners - Ram Bahadur Mouni (RSF Press, 2025)
This Paper explores the role of learner agency in promoting autonomous learning within the English language classrooms of Far Western University, Nepal. The paper basically focuses on how university students perceive and exercise learner agency, the factors shaping its development, and its reflection in actual classroom practices. Employing a qualitative ethnographic research method, information was collected over a year from four selected campuses through focus group discussions and classroom observations. The recorded data were manually transcribed, translated, and coded for thematic interpretation. The paper highlights that learner agency is minimally exercised, with student engagement largely confined to teacher-dominated instructional structures. Despite the availability of resources such as internet access, digital tools, and libraries, their integration into autonomous learning practices was limited. Students displayed low confidence, strong dependence on teachers, and anxiety driven by exam-oriented education systems. These attitudes, shaped by entrenched cultural norms and institutional rigidity, restricted students' participation in goal-setting, material selection, and self-evaluation. While isolated instances of student initiative, such as informal use of smartphones, were observed, they did not translate into sustained autonomous learning behaviors. The findings suggest the need for a multidimensional reform agenda that includes pedagogical shifts toward learner-centered strategies, institutional support for flexible curricula and assessment systems, and capacity-building for both students and teachers. This research offers valuable insights for policymakers, educators, and curriculum designers aiming to enhance learner agency and support lifelong learning competencies in the context of Nepalese higher education.